Prototipe deteksi banjir menggunakan sensor ultrasonik, dan water level sensor dengan notifikasi blynk - Muhammad Rega Alfiano Setiawan (Prodi Sistem Informasi Universitas Dharma Andalas, 2022)
Flood is a nature disaster which often happened in this world especially in Indonesia. This flood can be happened in flood vulnerable area, can cause disadvantage on the area. Flood can be happened cause high volume of water in river or lake, where the dam or irrigation can no longer accommodate the volume of water. The main causes of flooding are waterways that are blocked by al lot of garbage dumped carelessly by the community, illegal logging which can trigger flooding. Based on these problems, the researchers focus on the water level which during the rainy season. Therefore, the researchers made an IoT based flood detection system using two microcontrollers ultrasonic sensor and water level sensor as a measure of the water leve. The IoT-based ultrasonic sensor functions to send water level data which will be displayed by LCD, Blynk Notifications on android smartphones and also Buzzer alarms, and the Water level sensor serves to provide an alarm signal to the buzzer if water has touched the sensor. With the two flood detection tools, it will provide information faster, if the ultrasonic sensor has a signal problem, the water level sensor will give a warning in the form of an alarm on the buzzer when the water touches the sensor. The trial results of this prototype design have worked well to send alarms or signals with notifications on the Blynk application as a flood warning to the public.